In-vitro effects of Thymus munbyanus essential oil and thymol on human sperm motility and function. Issue 3 (September 2015) - Chikhoune, Amirouche; Stouvenel, Laurence; Iguer-Ouada, Mokrane; Hazzit, Mohamed; Schmitt, Alain; Lorès, Patrick; Wolf, Jean Philippe; Aissat, Kamel; Auger, Jacques; Vaiman, Daniel; Touré, Aminata
Abstract Traditional medicine has been used worldwide for centuries to cure or prevent disease and for male or female contraception. Only a few studies have directly investigated the effects of herbal compounds on spermatozoa. In this study, essential oil from Thymus munbyanus was extracted and its effect on human spermatozoa in vitro was analysed. Gas chromatography and Gas chromatography–mass spectrometry analyses identified 64 components, accounting for 98.9% of the composition of the oil. The principal components were thymol (52.0%), γ-terpinene (11.0%), ρ-cymene (8.5%) and carvacrol (5.2%). Freshly ejaculated spermatozoa was exposed from control individuals to various doses of the essential oil for different time periods, and recorded the vitality, the mean motility, the movement characteristics (computer-aided sperm analysis), the morphology and the ability to undergo protein hyperphosphorylation and acrosomal reaction, which constitute two markers of sperm capacitation and fertilizing ability. In vitro, both the essential oil extracted from T. munbyanus and thymol, the principal compound present in this oil, impaired human sperm motility and its capacity to undergo hyperphosphorylation and acrosome reaction. These compounds may, therefore, be of interest in the field of reproductive biology, as potential anti-spermatic agents.